Ti-W-series super-elastic metastable beta titanium alloy and preparation method and application thereof

By adding Zr/Sn elements to the Ti-W matrix, the Ti-W superelastic metastable β titanium alloy was prepared, which solved the problem of insufficient performance of the existing Ti-W alloy in the biomedical field, and achieved a new biomedical superelastic alloy with low elastic modulus and high biocompatibility, which was suitable for a variety of biomedical equipment.

CN119506656APending Publication Date: 2025-02-25DALIAN MARITIME UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411643160.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing Ti-W alloys have insufficient performance in the biomedical field, especially in terms of low elastic modulus and biocompatibility, and it is difficult to meet the needs of medical materials.

Method used

By adding Zr/Sn elements to the Ti-W matrix, a Ti-W-based superelastic metastable β-titanium alloy was prepared, and its components were optimized to be 20% W, 4-6% Zr, 6-8% Sn and the remaining amount of Ti and inevitable impurities were Ti. The new biomedical superelastic Ti-W-based alloy with low elastic modulus and high biocompatibility was prepared by arc smelting, homogenizing annealing, cold rolling and recrystallization annealing.

Benefits of technology

It realizes the low elastic modulus and high biocompatibility of Ti-W alloys, enhances its tensile strength and corrosion resistance, and is suitable for biomedical equipment such as orthodontic arches, orthopedic staples and endovascular stents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506656A_ABST
    Figure CN119506656A_ABST
Patent Text Reader

Abstract

The invention provides a Ti-W-series super-elastic metastable beta titanium alloy and a preparation method and application of the Ti-W-series super-elastic metastable beta titanium alloy. According to the Ti-W series super-elastic metastable beta titanium alloy, beta type titanium serves as a matrix, three elements of tungsten, zirconium and tin are added, and in the alloy components, by taking the total mass of raw material composition components of the material as 100%, the alloy components comprise, by mass, 20% of W, 4%-6% of Zr, 6%-8% of Sn and the balance Ti. The Ti-W metastable beta titanium alloy provided by the invention has the room-temperature super-elastic characteristic, also has the characteristics of high strength, good plasticity and the like, has the characteristics of low elastic modulus, excellent biocompatibility and the like, and has great application value in the field of biomedical treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of titanium alloys, and in particular to a Ti-W series superelastic metastable β titanium alloy and a preparation method and application thereof. Background Art

[0002] Titanium alloy has excellent mechanical properties, high corrosion resistance and good biocompatibility. It is one of the most suitable medical materials and is widely used in hard tissue implants, oral plastic surgery and vascular stents. However, it has been reported that the Ni ions in the commonly used Ni-Ti alloy have certain sensitization, which has caused people to worry about its long-term implant safety. Titanium alloy has great application value in the biomedical field because of its low elastic modulus and excellent biocompatibility. According to the organizational characteristics after annealing, titanium alloys can be divided into three types: α-Ti alloy, β-Ti alloy, and (α+β)-Ti alloy. Compared with α-Ti alloy (α+β)-Ti alloy, β-Ti alloy is composed of non-toxic elements, shows a lower elastic modulus, can avoid stress shielding phenomenon, and is currently a hot spot in the research of medical titanium alloys.

[0003] Tungsten has high melting point, high strength and low thermal expansion coefficient, and has been widely used in special steel, tungsten carbide-based hard alloy, heat-resistant and wear-resistant alloy, contact and heavy alloy fields; Ti-W alloy has low resistivity, good thermal stability and oxidation resistance, and is usually used as a diffusion barrier layer for Al, Cu and Ag wiring. The present invention mainly takes biomedical β-Ti-W alloy as the research object, and prepares a new biomedical superelastic Ti-W alloy with low elastic modulus and biocompatibility by adding Zr / Sn elements to the Ti-W matrix, expanding the category of biomedical materials to make up for the performance deficiencies of traditional Ti-W alloy in the biomedical field. Summary of the invention

[0004] The present invention provides a Ti-W series superelastic metastable β-titanium alloy and a preparation method and application thereof. Biomedical β-Ti-W series alloys are taken as research objects. A novel biomedical superelastic Ti-W series alloy with low elastic modulus and biocompatibility is prepared by adding Zr / Sn elements to a Ti-W matrix, thereby expanding the categories of biomedical materials and making up for the performance deficiencies of traditional Ti-W alloys in the biomedical field.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a Ti-W series superelastic metastable β-titanium alloy, with β-titanium as the matrix, and three elements of tungsten, zirconium and tin are added. The alloy composition is calculated by weight percentage: 20% of W element, 4-6% of Zr element, 6-8% of Sn element, and the remainder is Ti and inevitable impurities. The total amount of the inevitable impurities does not exceed 0.01-0.02%. The total amount of impurities is negligible in this application.

[0006] Furthermore, the tensile strength R of the Ti-W superelastic metastable β titanium alloy is m 752-958MPa, yield strength R p0.2 It is 323-906MPa, and the elastic modulus E is 42.8-73.5GPa.

[0007] Further, the Ti is ≥ 68%, preferably 68-70%;

[0008] When Ti is 70%, W is 20%, Zr is 4%, and Sn is 6%;

[0009] Or, when Ti is 68%, W is 20%, Zr is 4%, and Sn is 8%;

[0010] Or, or when Ti is 68%, W is 20%, Zr is 6%, and Sn is 6%.

[0011] Furthermore, in the Ti-W superelastic metastable β titanium alloy, calculated by weight percentage: W is 20%, Zr is 4%, Sn is 8%, Ti is 68% and inevitable impurities, the total amount of the inevitable impurities does not exceed 0.01-0.02%, and the total amount of impurities is negligible in this application.

[0012] The present invention also provides a method for preparing a Ti-W series superelastic metastable β titanium alloy, comprising the following steps:

[0013] S1: weighing raw materials according to the types of alloy element components, putting them into an arc melting furnace, and performing arc melting under argon protection to obtain a titanium alloy ingot;

[0014] S2: The titanium alloy ingot obtained in step S1 is cut into thin slices, and then subjected to vacuum homogenization annealing heat treatment, cold rolling and recrystallization annealing to obtain a Ti-W series superelastic metastable β titanium alloy.

[0015] Furthermore, the Ti raw material is single element titanium with a purity greater than or equal to 99.9%; the W raw material is single element tungsten with a purity greater than or equal to 99.9%; the Zr raw material is single element zirconium with a purity greater than or equal to 99.9%; and the Sn raw material is single element tin with a purity greater than or equal to 99.9%.

[0016] Furthermore, in step S2, the specific method of the vacuum homogenization post-annealing treatment is:

[0017] The titanium alloy ingot obtained by smelting is cut into thin slices of 2±0.05 mm and then subjected to homogenization treatment. The homogenization annealing temperature is 1000-1150° C. and the holding time is 6±0.5 h.

[0018] Furthermore, in step S2, after the cold rolling treatment, a titanium alloy sheet is obtained, and the deformation amount of the titanium alloy sheet in the thickness direction is less than or equal to 50%.

[0019] Further, in step S2, the specific method of the recrystallization annealing is:

[0020] The titanium alloy plate obtained after cold rolling is cut into tensile specimens with a set width and a set thickness, and then subjected to recrystallization treatment. The heat treatment temperature is 750-850°C, the holding time is 30±5min, and the heat treatment temperature is preferably 750-850°C.

[0021] Furthermore, the tensile specimen has a thickness of 1 mm and a width of 2 mm.

[0022] The Ti-W superelastic metastable β titanium alloy provided by the present invention can be applied to the biomedical field. Specifically, the superelasticity of the Ti-W superelastic metastable β titanium alloy is widely used in biomedical equipment, such as orthodontic dental arches, orthopedic nails and intravascular stents.

[0023] In summary, the present invention has the following beneficial effects:

[0024] First, the present invention provides a Ti-W superelastic metastable β titanium alloy, wherein the Ti content is relatively high, not less than 68% by mass percentage, and the W content is 20% by mass percentage. The W element is a β phase stabilizing element. Adding W to the titanium alloy can reduce the deformation temperature of the titanium alloy and increase its anti-distortion ability, making the obtained Ti-W alloy harder, heat-resistant and wear-resistant, and improving the compressive strength and toughness of the titanium alloy. In addition, the addition of the W element to the titanium alloy can effectively improve the corrosion resistance of the titanium alloy, and a titanium alloy material with high corrosion resistance, high strength and high temperature stability can be manufactured. The addition of the Zr element can increase the recoverable strain, and the addition of the Sn element can reduce the phase transition point. Zr and Sn are neutral elements, have a large solubility in both α-Ti and β-Ti, and play a role in solid solution strengthening. Zr and Sn can improve the room temperature tensile strength and high temperature tensile properties of titanium and titanium alloys, reduce the β phase transition point; reduce the volume fraction of the ω phase, and improve the corrosion resistance and recoverable strain of titanium and titanium alloys.

[0025] Second, the preparation method of the Ti-W series titanium alloy of the present invention is simple and easy. Each element is weighed according to the mass percentage, and an arc melting furnace is used for multiple times under an argon atmosphere. After cooling, an ingot is obtained, and then the ingot is homogenized at a high temperature, water-cooled to room temperature, and then cold-rolled and recrystallized. The heat treatment temperature is 750-850°C. This temperature is relatively moderate, which is conducive to energy saving, and the aging time is as short as 30 minutes, which can further save energy, time cost, and equipment cost while maintaining stable and consistent performance.

[0026] Third, the elastic modulus E of the Ti-W superelastic metastable β titanium alloy of the present invention is 42.8-73.5GPa, which is significantly lower than the tensile elastic modulus (55-110GPa) of commonly used titanium alloys and close to the elastic modulus of human bones (~30GPa), which can effectively alleviate the implant failure induced by the mismatch of elastic modulus between the implant and human bones. In addition, the superelasticity of the Ti-W superelastic metastable β titanium alloy is widely used in biomedical equipment, such as orthodontic arches, orthopedic nails and intravascular stents. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0028] Figure 1 The present invention is a technical roadmap for the preparation process of the Ti-W superelastic alloy plate;

[0029] Figure 2 The microstructure diagram of the Ti-W superelastic metastable β titanium alloy according to Example 1 of the present invention;

[0030] Figure 3 The cyclic tensile curve of the Ti-W superelastic metastable β titanium alloy in Example 1 of the present invention;

[0031] Figure 4 The microstructure diagram of the Ti-W superelastic metastable β titanium alloy according to Example 2 of the present invention;

[0032] Figure 5 The cyclic tensile curve of the Ti-W superelastic metastable β titanium alloy according to Example 2 of the present invention;

[0033] Figure 6 The microstructure diagram of the Ti-W superelastic metastable β titanium alloy according to Example 3 of the present invention;

[0034] Figure 7The cyclic tensile curve of the Ti-W superelastic metastable β titanium alloy according to Example 3 of the present invention;

[0035] Figure 8 This is the tensile curve of the Ti-W superelastic metastable β titanium alloy after recrystallization of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The weight ratios of the components of the Ti-W metastable β titanium alloy with superelastic properties of the present invention are: W 20%, Zr 4-6%, Sn 6-8%, and the balance is Ti and inevitable impurities, the total amount of the inevitable impurities does not exceed 0.01-0.02%, and the total amount of impurities is negligible in this application. The present invention includes only four elements, Ti, W, Zr, and Sn, through reasonable component design, and at the same time, the alloy structure is regulated by homogenization, cold rolling deformation and subsequent heat treatment, so as to effectively improve the X-ray visibility and tensile strength of the titanium alloy, reduce the elastic modulus, and have the characteristic of recoverable strain.

[0038] Example

[0039] Example 1

[0040] Ingredient ratio: The raw material with a purity of 99.9% is selected. The weight ratios of the components of the Ti-W-Zr-Sn alloy with superelastic properties in this embodiment are: Ti 70%, W 20%, Zr 4%, Sn 6%.

[0041] Prepared by the following preparation method (such as Figure 1 ):

[0042] S1: Weigh high-purity titanium, high-purity tungsten, high-purity zirconium and high-purity tin according to the ratio, load them into an arc melting furnace, and then perform arc melting in an argon atmosphere with an induction current of 100-400A. After the alloy is completely melted, continue electromagnetic stirring for 3 minutes, cool to obtain an ingot, and repeat the melting for 6 times to obtain a titanium alloy ingot.

[0043] S2: The titanium alloy ingot is placed in a muffle furnace and homogenized at 1000 °C for 6 h, and then quenched to room temperature;

[0044] The treated ingot was cut into 2 mm thin slices by wire cutting, the oxide scale on the surface was cleaned by sandpaper, and the ingot was rolled at room temperature with a total rolling deformation of 50% to obtain a 1 mm thick slice;

[0045] The rolled thin sheets were cut into strip samples with a thickness of 1 mm and a width of 2 mm by wire cutting. The oxide scale on the surface was then cleaned with sandpaper and heat treated. The samples were placed in a muffle furnace for heat treatment at 750°C, 800°C and 850°C, respectively, with a holding time of 30 min.

[0046] Alloy Testing:

[0047] After heat treatment at 750℃, 800℃ and 850℃, the alloy microstructures were obtained by testing with a GX51 metallographic microscope (Olympus, Japan). Figure 2 As shown. Figure 2 It can be seen that no obvious grain boundaries were found in the titanium alloy of this embodiment under 750℃ treatment, which may be because no recrystallization occurred at this temperature. After heat treatment at 800℃ and 850℃, obvious recrystallization grain boundaries appeared. The titanium alloy of this embodiment may begin to recrystallize at 800℃, and the grains have obvious growth phenomenon as the temperature rises. No obvious martensitic structure was found in the microstructure of the titanium alloy of this embodiment, and most of it was composed of the parent phase β phase. The plasticity was improved as much as possible while maintaining the strength of the alloy. In addition, the addition of Zr and Sn in this embodiment can reduce the phase transition point and increase the recoverable strain of the alloy.

[0048] The alloys obtained after heat treatment at 750°C, 800°C and 850°C were subjected to tensile strength R using a WDW-20 universal mechanical testing machine (Jinan Dongfang Experimental Instrument Co., Ltd.). m , yield strength R p0.2 , elastic modulus E, maximum recovery strain ε r According to GB / T 228.1-2021 "Tensile test of metallic materials - Part 1: Room temperature test method", the samples were subjected to quasi-static tensile test at room temperature, and the alloys obtained after heat treatment at 750℃, 800℃ and 850℃ were subjected to static tensile test. The engineering stress-strain curve and tensile cycle curve are shown in Figure 3 and Figure 8 As shown. It was measured that after heat treatment at 750℃, the tensile strength R m The yield strength is 914MPa, and the yield strength R p0.2 is 906MPa, the elastic modulus E is 53.2GPa, and the maximum recovery strain ε r After recrystallization at 800℃, the tensile strength R m The yield strength R is 790MPa. p0.2is 792MPa, the elastic modulus E is 43.2GPa, and the maximum recovery strain ε r After recrystallization at 850℃, the tensile strength R m The yield strength is 799MPa, and the yield strength R p0.2 is 797MPa, the elastic modulus E is 73.5GPa, and the maximum recovery strain ε r It is 2.08%, has excellent strength and certain plasticity, and has superelastic properties at room temperature.

[0049] Example 2

[0050] Ingredient ratio: The raw material with a purity of 99.9% is selected. The weight ratios of the components of the Ti-W-Zr-Sn alloy with superelastic properties in this embodiment are: Ti 68%, W 20%, Zr 4%, Sn 8%.

[0051] Prepared by the following preparation method (such as Figure 1 ):

[0052] S1: Weigh high-purity titanium, high-purity tungsten, high-purity zirconium and high-purity tin according to the ratio, load them into an arc melting furnace, and then perform arc melting in an argon atmosphere with an induction current of 100-400A. After the alloy is completely melted, continue electromagnetic stirring for 3 minutes, cool to obtain an ingot, and repeat the melting for 6 times to obtain a titanium alloy ingot.

[0053] S2: The titanium alloy ingot is placed in a muffle furnace and homogenized at 1000 °C for 6 h, and then quenched to room temperature;

[0054] The treated ingot was cut into 2 mm thin slices by wire cutting, the oxide scale on the surface was cleaned by sandpaper, and the ingot was rolled at room temperature with a total rolling deformation of 50% to obtain a 1 mm thick slice;

[0055] The rolled thin sheets were cut into strip samples with a thickness of 1 mm and a width of 2 mm by wire cutting. The oxide scale on the surface was then cleaned with sandpaper and heat treated. The samples were placed in a muffle furnace for heat treatment at 750°C, 800°C and 850°C, respectively, with a holding time of 30 min.

[0056] Alloy Testing:

[0057] After heat treatment at 750℃, 800℃ and 850℃, the alloy microstructures were obtained by testing with a GX51 metallographic microscope (Olympus, Japan). Figure 4 As shown, from Figure 4It can be seen that no obvious recrystallization grain boundaries were found in the titanium alloy of this embodiment under 750℃ treatment, which may be because no recrystallization occurred at this temperature. After heat treatment at 800℃ and 850℃, obvious recrystallization grain boundaries appeared. The titanium alloy of this embodiment may begin to recrystallize at 800℃, and the grains grow significantly as the temperature rises. No obvious martensitic structure was found in the microstructure of the titanium alloy of this embodiment, and most of it was composed of the parent phase β phase. The plasticity was improved as much as possible while maintaining the strength of the alloy. In addition, the addition of Zr and Sn in this embodiment can reduce the phase transition point and increase the recoverable strain of the alloy.

[0058] The alloys obtained after heat treatment at 750°C, 800°C and 850°C were subjected to tensile strength R using a WDW-20 universal mechanical testing machine (Jinan Dongfang Experimental Instrument Co., Ltd.). m , yield strength R p0.2 , elastic modulus E, maximum recovery strain ε r According to GB / T 228.1-2021 "Tensile test of metallic materials - Part 1: Room temperature test method", the samples were subjected to quasi-static tensile test at room temperature, and the alloys obtained after heat treatment at 750℃, 800℃ and 850℃ were subjected to static tensile test. The engineering stress-strain curve and tensile cycle curve are shown in Figure 5 and Figure 8 As shown. It was measured that after the alloy was recrystallized at 750℃, the tensile strength R m The yield strength is 958MPa, and the yield strength R p0.2 is 865MPa, the elastic modulus E is 54.8GPa, and the maximum recovery strain ε r is 4.83%. After recrystallization at 800℃, the tensile strength R m The yield strength is 905MPa, and the yield strength R p0.2 is 633MPa, the elastic modulus E is 44.8GPa, and the maximum recovery strain ε r After recrystallization at 850℃, the tensile strength R m The yield strength R is 942MPa. p0.2 is 811MPa, the elastic modulus E is 63.8GPa, and the maximum recovery strain ε r It is 4.22%, has excellent strength and certain plasticity, and has superelastic properties.

[0059] Example 3

[0060] Ingredient ratio: The raw material with a purity of 99.9% is selected. The weight ratios of the components of the Ti-W-Zr-Sn alloy with superelastic properties in this embodiment are: Ti 68%, W 20%, Zr 6%, Sn 6%.

[0061] Prepared by the following preparation method (such as Figure 1 ):

[0062] S1: Weigh high-purity titanium, high-purity tungsten, high-purity zirconium and high-purity tin according to the ratio, load them into the arc melting furnace, and then perform arc melting in an argon atmosphere with an induction current of 100-400A. After the alloy is completely melted, continue electromagnetic stirring for 3 minutes, cool to obtain an ingot, and repeat the melting for 6 times to obtain a titanium alloy ingot.

[0063] S2. The titanium alloy ingot was placed in a muffle furnace, homogenized at 1000°C for 6 h, and then quenched in water to room temperature;

[0064] The treated ingot was cut into 2 mm thin slices by wire cutting, the oxide scale on the surface was cleaned by sandpaper, and the ingot was rolled at room temperature with a total rolling deformation of 50% to obtain a 1 mm thick slice;

[0065] The rolled thin sheets were cut into strip samples with a thickness of 1 mm and a width of 2 mm by wire cutting. The oxide scale on the surface was then cleaned with sandpaper and heat treated. The samples were placed in a muffle furnace for heat treatment at 750°C, 800°C and 850°C, respectively, with a holding time of 30 min.

[0066] Alloy Testing:

[0067] After heat treatment at 750℃, 800℃ and 850℃, the alloy microstructures were obtained by testing with a GX51 metallographic microscope (Olympus, Japan). Figure 6 As shown, from Figure 6 It can be seen that the titanium alloy of this embodiment has obvious recrystallization grain boundaries when treated at 750°C. The titanium alloy of this embodiment may begin to recrystallize at 750°C, and the grains have obvious growth phenomenon as the temperature rises. The titanium alloy microstructure of this embodiment does not have obvious martensite structure, and most of it is composed of the parent phase β phase. The plasticity is improved as much as possible while maintaining the strength of the alloy. In addition, the addition of Zr and Sn in this embodiment can reduce the phase transition point and increase the recoverable strain of the alloy.

[0068] The alloys obtained after heat treatment at 750°C, 800°C and 850°C were subjected to tensile strength R using a WDW-20 universal mechanical testing machine (Jinan Dongfang Experimental Instrument Co., Ltd.). m , yield strength R p0.2 , elastic modulus E, maximum recovery strain ε rAccording to GB / T 228.1-2021 "Tensile test of metallic materials - Part 1: Room temperature test method", the samples were subjected to quasi-static tensile test at room temperature, and the alloys obtained after heat treatment at 750℃, 800℃ and 850℃ were subjected to static tensile test. The engineering stress-strain curve and tensile cycle curve are shown in Figure 7 and Figure 8 As shown in the figure, the tensile strength R m The yield strength is 803MPa, and the yield strength R p0.2 is 323MPa, the elastic modulus E is 46GPa, and the maximum recovery strain ε r 2.49%, after recrystallization at 800℃, the tensile strength R m The yield strength R is 752MPa. p0.2 is 377MPa, the elastic modulus E is 42.8GPa, and the maximum recovery strain ε r After recrystallization at 850℃, the tensile strength R m The yield strength R is 839MPa. p0.2 is 440MPa, the elastic modulus E is 62.4GPa, and the maximum recovery strain ε r It is 2.89%, has excellent strength and certain plasticity, and has superelastic properties.

[0069] Comparative Example

[0070] The difference between the comparative example and the embodiment is that the comparative example has different composition ratios: specifically:

[0071] Component ratio: The raw material with a purity of 99.9% is selected. The weight ratios of the components of the Ti-W alloy with superelastic properties in this comparative example are: Ti 75%, W 25%.

[0072] The relevant performance tests were performed using the test method of Example 1 above.

[0073] The alloys obtained after heat treatment at 750℃ and 850℃ were tested for tensile strength R using a WDW-20 universal mechanical testing machine (Jinan Dongfang Experimental Instrument Co., Ltd.). m , yield strength R p0.2 , elastic modulus E, maximum recovery strain ε r performance testing.

[0074] After treatment at 750℃ for 30min, the performance indicators of Ti-W alloy are as follows: tensile strength R m The yield strength R is 643MPa. p0.2 is 520MPa, the elastic modulus E is 99GPa, and the maximum recovery strain ε rAfter recrystallization at 800℃, the tensile strength R m The yield strength R is 631MPa. p0.2 is 447MPa, the elastic modulus E is 122GPa, and the maximum recovery strain ε r After recrystallization at 850℃, the tensile strength R m The yield strength R is 643MPa. p0.2 is 450MPa, the elastic modulus E is 92GPa, and the maximum recovery strain ε r It is 2.7%.

[0075] It can be seen from Examples 1-3 that when the Sn content is 6-8%, as the Sn content gradually increases, the tensile strength increases, the yield strength decreases, the elastic modulus decreases, and the maximum recoverable strain increases. When the Zr content is 4-6%, as the Zr content gradually increases, the tensile strength decreases, the yield strength decreases, the elastic modulus decreases, and the maximum recoverable strain increases. The combined effect of an appropriate amount of 4% Zr and 8% Sn can increase the recoverable strain to more than 4%, thereby improving the superelastic properties of the titanium alloy.

[0076] The comparative example does not add Zr and Sn. Compared with Example 1, after heat treatment at 750°C, its tensile strength R m , yield strength R p0.2 , maximum recovery strain ε r After heat treatment at 800℃ and 850℃, the recoverable strain of the comparative example increased, but its tensile strength R m , yield strength R p0.2 , the elastic modulus E is poorer than that of Example 1 and Example 3;

[0077] Compared with Example 2, the recoverable strain of Example 2 can reach up to 4.83%, while the recoverable strain of the comparative example is only 2.8%. Therefore, compared with the comparative example, Examples 1-3 effectively improve the X-ray visibility and tensile strength of the titanium alloy, reduce the elastic modulus, and have recoverable strain.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A Ti-W superelastic metastable β titanium alloy, characterized in that: Beta-titanium is used as the matrix, and three elements, tungsten, zirconium and tin, are added. In the alloy composition, taking the total mass of the raw material components of the material as 100%, the components and their mass percentages are: 20% W, 4-6% Zr, 6-8% Sn, and the balance is Ti.

2. The Ti-W superelastic metastable β titanium alloy according to claim 1, characterized in that: The tensile strength R of the Ti-W superelastic metastable β titanium alloy m 752-958MPa, yield strength R p0.2 It is 323-906MPa, and the elastic modulus E is 42.8-73.5GPa.

3. The Ti-W superelastic metastable β titanium alloy according to claim 1, characterized in that: When Ti is 70%, W is 20%, Zr is 4%, and Sn is 6%; Or, when Ti is 68%, W is 20%, Zr is 4%, and Sn is 8%; Or, when Ti is 68%, W is 20%, Zr is 6%, and Sn is 6%.

4. The method for preparing the Ti-W superelastic metastable β titanium alloy according to any one of claims 1 to 3, characterized in that: The steps include: S1: weighing raw materials according to the types of alloy element components, putting them into an arc melting furnace, and performing arc melting under argon protection to obtain a titanium alloy ingot; S2: The titanium alloy ingot obtained in step S1 is cut into thin slices, and then subjected to vacuum homogenization annealing heat treatment, cold rolling and recrystallization annealing to obtain a Ti-W series superelastic metastable β titanium alloy.

5. The preparation method according to claim 4, characterized in that: The Ti raw material is single element titanium with a purity greater than or equal to 99.9%; the W raw material is single element tungsten with a purity greater than or equal to 99.9%; the Zr raw material is single element zirconium with a purity greater than or equal to 99.9%; and the Sn raw material is single element tin with a purity greater than or equal to 99.9%.

6. The preparation method according to claim 4, characterized in that: In step S2, the specific method of the vacuum homogenization post-heat treatment is: The titanium alloy ingot obtained by smelting is cut into thin slices of 2±0.05 mm and then subjected to homogenization treatment. The homogenization annealing temperature is 1000-1150° C. and the holding time is 6±0.5 h.

7. The preparation method according to claim 4, characterized in that: In step S2, after the cold rolling treatment, a titanium alloy sheet is obtained, and the deformation amount of the titanium alloy sheet in the thickness direction is less than or equal to 50%.

8. The preparation method according to claim 4, characterized in that: In step S2, the specific method of the recrystallization annealing is: The titanium alloy sheet obtained after the cold rolling treatment is cut into tensile specimens with a set width and a set thickness, and then subjected to a recrystallization treatment, with a recrystallization temperature of 750-850° C. and a holding time of 30±5 min.

9. The preparation method according to claim 8, characterized in that: The tensile specimen has a thickness of 1±0.05 mm and a width of 2±0.05 mm.

10. Use of the Ti-W superelastic metastable β titanium alloy according to any one of claims 1 to 3 in biomedicine, such as orthodontic dental arches, orthopedic nails and intravascular stents.